HAK ASUH (HADLANAH) ISTERI MURTAD MENURUT HUKUM POSITIF DAN HUKUM ISLAM (Analisis atas Putusan Pengadilan Agama Pangkalan Kerinci No: 13/Pdt.G/2009/PA.Pkc) - Aris Bintania (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
Peradilan Agama is a court of Islamic Community in Indonesia and regarded as one of court for people who are seeking for the justice, especially after the ratification of Islamic Court Law Number 7 in 1989. The aim of the ratification this Islamic Court Law is to unity and to terminate the variety source of regulation that regulate structure, competency and procedural law of Islamic Court in Indonesia. Nevertheless, until now, there are still many source of regulation, even though that Islamic Court Law had been modify and revised by Ordinance Number 3 in 2006. Ironically the rule of Section 54 of Islamic Court Law still enforce procedural law of national court which its source is very multifarious, beside the very minimum special procedural law were ruled. As a result the source of procedural law in Islamic Court is still multifarious. The variety source of Islamic Court Regulation, especially procedural law, caused many problems and contradictions. On one side Peradilan Agama is a national court that must be compatible with nationality spirit but in other side so Peradilan Agama is Islamic Court that should always obeys Islamic norms and codes that sometimes not compatible with nationality spirit and impossible to synchronize. This paper concern about this issues and attempt to analyze from the law and regulation way of view that completed with fiqh analysis.